ESIPT-based ratiometric fluorescence probe for the intracellular imaging of peroxynitrite. Issue 71 (17th August 2018) - Wu, Luling; Wang, Yang; Weber, Maria; Liu, Liyuan; Sedgwick, Adam C.; Bull, Steven D.; Huang, Chusen; James, Tony D.
Abstract : In this work, we set out to develop an ER directed ESIPT-based ONOO − ratiometric fluorescent probe (ABAH-LW ). Abstract : In this work, we set out to develop an endoplasmic reticulum (ER) directed ESIPT-based ONOO − ratiometric fluorescent probe (ABAH-LW ).ABAH-LW was synthesized in four steps and found to have a high sensitivity and selectivity towards the detection of ONOO − .ABAH-LW was able to detect low concentrations of ONOO − (limit of detection = 21.4 nM) within seconds producing a ratiometric change in fluorescence intensity.ABAH-LW further demonstrated the ability to ratiometrically image endogenous and exogenous ONOO − in HeLa cells. Moreover, co-localization experiments were carried out using commercially available ER-Tracker Red, Lyso-Tracker Red and Mito-Tracker-Red, which were co-stained withABAH-LW in HeLa cells. For ER-Tracker Red, Pearson's correlation co-efficient of 0.93 was determined and 3D surface plot analysis illustrated a large overlap betweenABAH-LW and ER-Tracker Red using both red and blue channels. In addition some co-localisation with Mito-Tracker Red andABAH-LW was observed (0.73).